2016
DOI: 10.1039/c5mt00251f
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of zinc to platelet behaviour during haemostasis and thrombosis

Abstract: Platelets are the primary cellular determinants of haemostasis and pathological thrombus formation leading to myocardial infarction and stroke. Following vascular injury or atherosclerotic plaque rupture, platelets are recruited to sites of damage and undergo activation induced by a variety of soluble and/or insoluble agonists. Platelet activation is a multi-step process culminating in the formation of thrombi, which contribute to the haemostatic process. Zinc (Zn(2+)) is acknowledged as an important signallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 154 publications
0
39
0
1
Order By: Relevance
“…It has been understood for decades now that zinc is capable of enhancing platelet activity and aggregation [ 46 , 47 ]. Recently it was shown that the effect of zinc on platelets is mediated through Protein kinase C (PKC)-mediated tyrosine phosphorylation of platelet proteins [ 48 , 49 ]. Exogenous zinc treatment (at millimolar concentration range) induced zinc entry into the platelet cytosol and time-dependent (within 30 min) stimulation of tyrosine phosphorylation on certain high molecular weight proteins which could be blocked by PKC inhibitors.…”
Section: The Phases Of Wound Healing and Zinc’s Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been understood for decades now that zinc is capable of enhancing platelet activity and aggregation [ 46 , 47 ]. Recently it was shown that the effect of zinc on platelets is mediated through Protein kinase C (PKC)-mediated tyrosine phosphorylation of platelet proteins [ 48 , 49 ]. Exogenous zinc treatment (at millimolar concentration range) induced zinc entry into the platelet cytosol and time-dependent (within 30 min) stimulation of tyrosine phosphorylation on certain high molecular weight proteins which could be blocked by PKC inhibitors.…”
Section: The Phases Of Wound Healing and Zinc’s Impactmentioning
confidence: 99%
“…Platelets contain alpha-granules, which carry a plethora of proteins and factors, such as Chemokine (C-X-C motif) ligand 1 (CXCL1, GRO-α (growth regulated α protein), CXCL4, CXCL5 (ENA-78 ,epithelial-derived neutrophil-activating protein 78), CXCL7 (PPBP (Pro-Platelet basic protein), β-TG (Beta-Thromboglobulin), CTAP-III (connective tissue activating peptide III), NAP-2 (neutrophil-activating peptide-2)), CXCL8 (IL-8, interleukin-8), CXCL12 (SDF-1α, stromal cell-derived factor-1α), Chemokine (C-C motif) ligand 2 (CCL2, MCP-1(monocyte chemoattractant protein-1)), CCL3 (MIP-1α, macrophage inflammatory protein 1-α) and CCL5 (RANTES, regulated upon activation normal T cell expressed and secreted); factors capable of recruiting and activating innate immune cells to the wound site [ 51 ]. It has been shown that zinc induces alpha-granule release [ 48 ]. These studies suggest that platelets and zinc play an important role in initiating the inflammatory phase of wound healing.…”
Section: The Phases Of Wound Healing and Zinc’s Impactmentioning
confidence: 99%
“…Some Zn 2+ may be incorporated when the Zn 2+ -bound fibrinogen-coagulation factor XIII(a 2 ) complex enters the platelet through binding to fibrinogen receptors. 37 However the main mechanism for Zn 2+ entry into platelets is likely to be through Zn 2+ transporters (as reviewed by Taylor and Pugh); 38 the exact mechanism however remains to be elucidated. When platelets are activated, up to half of the α-granule Zn 2+ pool is released.…”
Section: Zn 2+ Repartition In Plasmamentioning
confidence: 99%
“…However, in more recent years, the importance of Zn 2+ in coagulation and regulation of platelet function has started to emerge. 13 , 38 , 42 A variety of blood proteins involved in coagulatory processes have been identified as Zn 2+ -binding proteins. In many cases the ability to bind Zn 2+ has the potential to influence their activities and impact upon haemostasis.…”
Section: Relevance Of Zn 2+ In Coagulation Controlmentioning
confidence: 99%
“…In contrast to the role of cations (i.e., Ca 2+ , K + , and Zn 2+ ) [13], the contribution(s) of anions to platelet activation remains unclear. Anion channels perform diverse functions including regulatory volume decrease [4], phosphatidylserine exposure [5], and ATP release [6].…”
Section: Introductionmentioning
confidence: 99%